(untitled) (Itinera, 2023)
Metaphor has often been seen as tightly associated with both aesthetics and cognition, as well as with other aesthetic and cognitive phenomena such as imagination, symbol, allegory, analogy and simile. This article offers a theory of metaphor that accounts for such aesthetic and cognitive associations. The theory is based on a suitably interpreted version of a tool originally developed in an epistemic context, viz. Floridi and Sanders’ method of abstraction.